Analisis Faktor-Faktor Produksi Usaha Pengembangan Sapi Potong Di Kabupaten Teluk Bintuni : Analysis of Beef Cattle Development Business Production Factors in Teluk Bintuni District - Iwung Sri Suryaningsih; Sientje Daisy Rumetor; Andoyo Supriyantono; Irba Unggul Warsono (Fakultas Peternakan Universitas Papua, 2022)
Abstract The success of animal husbandry depends on three elements commonly referred to as the production triangle, namely seeds, feed and management. In addition, the technosocioeconomic characteristics of farmers greatly affect the income of farmers. The research objective was to analyze the factors of production (seed, feed and management) and provide a concept for a good beef cattle breeding system in the development of beef cattle in Teluk Bintuni Regency. This type of research is a descriptive quantitative research. A total of 53 samples were taken purposively with the same inter-district maintenance system and had the largest population, the maintenance scale ranged from 3-5 beef cattle and 5 years and above of farming experience. The variables observed were seed factors, feed factors, management factors and income. The data obtained were analyzed by multiple linear regression. The results showed that the beef cattle raised were Balinese breed with male body weight 318 - 396 kg and female 285 - 326 kg at the age of ± 3 years. The availability of adequate forage and land availability is very potential for extensive maintenance patterns, but for the carrying capacity of pasture is not yet meet te requrement. Maintaining an extensive pattern has the risk of livestock infected by worms (endoparasites) around 62.26%. Marketing is carried out through collector traders (75.47%). The income of farmers is Rp. 9,704,643 - Rp. 14,069,978 per year. The price of seeds, the selling price of livestock, the price of feed, the scale of the business, the age of the farmer, experience and education, together have an effect on the income of the farmers with an Adjusted R Square value of 0.997. Keywords: Beef cattle development; Production factors; Teluk bintuni Abstrak Keberhasilan usaha peternakan bergantung pada tiga unsur yang biasa disebut dengan segitiga produksi yaitu bibit, pakan, dan pengelolaan. Selain itu, karakteristik teknososioekonomi peternak, sangat berpengaruh terhadap pendapatan peternak. Tujuan penelitian adalah menganalisis faktor-faktor produksi (bibit, pakan dan pengelolaan) dan memberikan konsep sistem pemeliharaan ternak sapi potong yang baik dalam pengembangan sapi potong di Kabupaten Teluk Bintuni. Jenis penelitian ini adalah penelitian kuantatif deskriptif. Sebanyak 53 sampel diambil secara purposif dengan sistem pemeliharaan antar distrik sama dan memiliki populasi terbanyak, skala pemeliharaan berkisar 3-5 ekor serta pengalaman beternak 5 tahun keatas. Variabel yang diamati yaitu faktor bibit, faktor pakan, faktor pengelolaan dan pendapatan. Data yang diperoleh dianalisis dengan regresi linear berganda. Hasil penelitian menunjukkan bahwa sapi potong yang dipelihara adalah bangsa sapi bali dengan bobot badan jantan 318 – 396 kg dan betina 285 - 326 kg pada umur ± 3tahun. Ketersediaan hijauan cukup dan ketersediaan lahan sangat potensial untuk pola pemeliharaan ekstensif, namun untuk daya tampung padang pegembalaan belum sesuai. Pemeliharaan pola ekstensif beresiko ternak terinfeksi cacing (endoparasit) sekitar (62,26%). Pemasaran dilakukan melalui pedagang pengumpul (75,47%). Pendapatan peternak berkisar Rp. 9.704.643 – Rp. 14.069.978 per tahun. Harga bibit, harga jual ternak, harga pakan, skala usaha, umur petani, pengalaman dan pendidikan, secara bersama berpengaruh terhadap pendapatan peternak dengan nilai Adjusted R Square sebesar 0.997. Kata kunci: Faktor produksi; Pengembangan sapi potong;Teluk Bintuni